A Pre-Lapita Structure at Apalo, Arawe Islands, Papua New Guinea. (3rd April 2017) - Specht, Jim; Gosden, Chris; Lentfer, Carol; Jacobsen, Geraldine; Matthews, Peter J.; Lindsay, Sue
ABSTRACT: Stilt structures in the inter-tidal zone or over shallow water on fringing reefs are widely accepted as a feature of settlements of the Lapita cultural complex in Near Oceania. Claims for similar structures in a pre-Lapita context at the Apalo site in the Arawe Islands, New Britain, Papua New Guinea, have been queried on several grounds. Re-evaluation of the Apalo evidence, together with 10 additional AMS radiocarbon dates, establishes human activity associated with some form of structure and possibly with a ground stone axe about 400–500 years before the Lapita pottery occupation. The paucity of occupational refuse suggests a non-residential structure perhaps associated with water transport. Comparisons with the older Dongan midden site in the Sepik-Ramu basin suggest stilt structures were probably used there as well. An apparent shift in depositional processes between the pre-Lapita and Lapita use of Apalo could reflect changed sea conditions arising from increased ENSO activity.